Cement Types, Composition, Uses and Advantages of Nanocement, Environmental Impact on Cement Production, and Possible Solutions - S. P. Dunuweera; R. M. G. Rajapakse (Advances in Materials Science and Engineering)
We first discuss cement production and special nomenclature used by cement industrialists in expressing the composition of their cement products. We reveal different types of cement products, their compositions, properties, and typical uses. Wherever possible, we tend to give reasons as to why a particular cement type is more suitable for a given purpose than other types. Cement manufacturing processes are associated with emissions of large quantities of greenhouse gases and environmental pollutants. We give below quantitative and qualitative analyses of environmental impact of cement manufacturing. Controlling pollution is a mandatory legal and social requirement pertinent to any industry. As cement industry is one of the biggest CO2 emitters, it is appropriate to discuss different ways and means of CO2 capture, which will be done next. Finally, we give an account of production of nanocement and advantages associated with nanocement. Nanofillers such as nanotitania, nanosilica, and nanoalumina can be produced in large industrial scale via top-down approach of reducing size of naturally available bulk raw materials to those in the nanorange of 1 nm–100 nm. We mention the preparation of nanotitania and nanosilica from Sri Lankan mineral sands and quartz deposits, respectively, for the use as additives in cement products to improve performance and reduce the amount and cost of cement production and consequent environmental impacts. As of now, mineral sands and other treasures of minerals are exported without much value addition. Simple chemical modifications or physical treatments would add enormous value to these natural materials. Sri Lanka is gifted with highly pure quartz and graphite from which silica and graphite nanoparticles, respectively, can be prepared by simple size reduction processes. These can be used as additives in cements. Separation of constituents of mineral sands is already an ongoing process.